1969
DOI: 10.1139/z69-077
|View full text |Cite
|
Sign up to set email alerts
|

Grain aphids in New Brunswick. IV. Effects of malathion and 2,4-D amine on aphid populations and on yields of oats and barley

Abstract: Aphid populations on oats (Fundy and Stormont) and barley (Charlottetown 80) were studied in the field and yields of these grains examined under the different levels of aphid infestation resulting from applications of malathion and 2,4-D amine to the crop.Two species of aphid, Rhopalosiphum padi (L.) and Macrosiphum avenae (Fab.), occurred on the grains, and the greatest populations developed on barley. In all cases highest numbers were associated with applications of 2,4-D amine. Applications of this herbicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For instance, 2-4D on barley reduced fecundity in two species of grain aphids, Rhopalosiphum padi and Macrosiphum avenae (14), but applied to corn increased fecundity of corn leaf aphids, Rhopalosiphum maydis (15), suggesting an improvement in the quality of food for the insect. Other herbicides have been tested with fewer insects, and results vary.…”
Section: Induction Of Resistance By Growth Regulators and Herbicidesmentioning
confidence: 99%
“…For instance, 2-4D on barley reduced fecundity in two species of grain aphids, Rhopalosiphum padi and Macrosiphum avenae (14), but applied to corn increased fecundity of corn leaf aphids, Rhopalosiphum maydis (15), suggesting an improvement in the quality of food for the insect. Other herbicides have been tested with fewer insects, and results vary.…”
Section: Induction Of Resistance By Growth Regulators and Herbicidesmentioning
confidence: 99%
“…The positive effect on aphids has been attributed to reduced predation under field conditions, probably due to the altered food quality of treated host plants,4, 14 or to insecticidal effects of the herbicide on predators 15. 16…”
Section: Introductionmentioning
confidence: 99%
“…There is good evidence that plant leaves are capable of increasing the rate of photosynthesis in response to defoliation (Alderfer & Eagles 1976), shading of adjacent leaves (Thorne & Koller 1974), or the presence of aphids on adjacent leaves (Way & Cammell 1970). A number of studies have demonstrated decreased yield of a specific organ (Adams & Drew 1969;Rockwood 1973;Stephenson 1980) or of the plant as a whole (Detling et al 1980;Smith & Odum 1981). A number of studies have demonstrated decreased yield of a specific organ (Adams & Drew 1969;Rockwood 1973;Stephenson 1980) or of the plant as a whole (Detling et al 1980;Smith & Odum 1981).…”
Section: Introductionmentioning
confidence: 99%